Paired comparisons of mutational profiles before and after brachytherapy in asian uveal melanoma patients - Woo Seung Lee (Nature Portfolio, 2021)
Abstract Uveal melanoma(UM) is the most common primary intraocular malignancy in adults. However, the incidence of UM in Asia is 10 to 20 times less than in Western populations. Therefore, for the first time, we report our whole exome sequencing (WES) data analysis to discover differences in the molecular features of Asian and Western UM, and to determine the disparities between the primary tumor before brachytherapy and enucleated samples after brachytherapy. WES of 19 samples (13 primary tumors, 5 enucleation samples after brachytherapy, and 1 liver metastasis) from 13 patients diagnosed with UM and treated between 2007 and 2019 at the Yonsei University Health System (YUHS) were analyzed using bioinformatics pipelines. We identified significantly altered genes in Asian UM and changes in mutational profiles before and after brachytherapy using various algorithms. GNAQ, BAP1, GNA11, SF3B1 and CYSLTR2 were significantly mutated in Asian UM, which is similar that reported frequently in previous Western-based UM studies. There were also similar copy number alterations (M3, 1p loss, 6p gain, 8q gain) in both groups. In paired comparisons of the same patients, DICER1 and LRP1B were distinctly mutated only in tumor samples obtained after brachytherapy using rare-variant association tests (P = 0.01, 0.01, respectively). The mutational profiles of Asian UM were generally similar to the data from previous Western-based studies. DICER1 and LRP1B were newly mutated genes with statistical significance in the regrowth samples after brachytherapy compared to the primary tumors, which may be related to resistance to brachytherapy.